2016
DOI: 10.1021/jacs.6b07610
|View full text |Cite
|
Sign up to set email alerts
|

Regioisomer-Specific Mechanochromism of Naphthopyran in Polymeric Materials

Abstract: Transformation of naphthopyran into a colored merocyanine species in polymeric materials is achieved using mechanical force. We demonstrate that the mechanochemical reactivity of naphthopyran is critically dependent on the regiochemistry, with only one particular substitution pattern leading to successful mechanochemical activation. Two alternative regioisomers with different polymer attachment points are demonstrated to be mechanochemically inactive. This trend in reactivity is accurately predicted by DFT cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
180
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 193 publications
(190 citation statements)
references
References 42 publications
2
180
0
Order By: Relevance
“…The advantage of the proposed method over existing triggering methods is the capability to achieve spatiotemporal control of mechanophore activation. In particular, while previous studies have demonstrated mechanochemical activation in bulk polymers using compression and tension (3,4,8,45), the HIFU-based triggering system demonstrated here is a remote energy source capable of localizing the region of activation and triggering polymer mechanochemistry noninvasively. These advances enable mechanoactivation of two different mechanophore systems.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The advantage of the proposed method over existing triggering methods is the capability to achieve spatiotemporal control of mechanophore activation. In particular, while previous studies have demonstrated mechanochemical activation in bulk polymers using compression and tension (3,4,8,45), the HIFU-based triggering system demonstrated here is a remote energy source capable of localizing the region of activation and triggering polymer mechanochemistry noninvasively. These advances enable mechanoactivation of two different mechanophore systems.…”
Section: Resultsmentioning
confidence: 94%
“…In this work, we evaluate the ability of HIFU to trigger polymer mechanochemistry in a polydimethylsiloxane (PDMS) elastomeric network through mechanical deformation. Our group has previously reported naphthopyran (NP) as a colorless mechanophore that undergoes electrocyclic ring opening, generating an orange-colored merocyanine in response to mechanical force (4). The visible color change associated with NP mechanoactivation provides a simple readout for initial investigations of the HIFU-triggered polymer mechanochemistry.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…[12] Fluorochromicm aterials with reversiblec olor changet riggered by external stimuli are an important category of smart materials. [13] Up to now,s everalt ypes of fluorochromic materials have been developed such as photochromic, [14] electrochromic, [15] thermochromic, [16] mechanochromic, [17] solvatochromic, [18] and vapochromic [19] materials. Among them, mechano-chromic materials with reversiblef luorescence change by mechanical stress have made rapid progress.…”
mentioning
confidence: 99%